PERAN PEMERINTAH KABUPATEN BREBES DALAM PEMBERDAYAAN PETERNAK ITIK - Yudha Ganang Permana; Turtiantoro .; Puji Astuti (Journal of Politic and Government Studies, 2015)
Abstract This research was conducted with government policy background Brebes through livestock services. In an attempt to realize the empowerment of duck breeders in Brebes, then diwujudkanlah policies and efforts of the government for the benefit of duck farmers scattered in Brebes who are members of farmer groups duck. This study focuses on the implementation in agriculture. Researchers used a qualitative research method that refers to the type of descriptive study. These research subjects are related parties and are involved in the implementation of policies to duck farmers who are members of the duck farmer groups including livestock services Brebes. The technique of collecting data through observation, interviews, documentation, literature and then analyzed through data reduction techniques, data presentation and verification / draw conclusions. These results indicate that the implementation of the aid to the farmer groups duck is not maximized in improving agricultural productivity and farm effectively, it is because the lack of technical guidance regarding the development of agriculture and animal husbandry. To fix this policy, of course, the need for improvement of both administrative and technical. Help plus, intensivity guidance from the Department related to the field of animal husbandry farms to the farmers, to maximize control systems, and infrastructure improvements. Keywords : Effectiveness, Policy, farm, duck farmers